Novel Miniature Transposable Elements in Thermophilic Synechococcus Strains and Their Impact on an Environmental Population - Nelson, William C. (American Society for Microbiology, 2012)
The genomes of the two closely related freshwater thermophilic cyanobacteria Synechococcus sp. strain JA-3-3Ab and Synechococcus sp. strain JA-2-3B′a(2-13) each host several families of insertion sequences (ISSoc families) at various copy numbers, resulting in an overall high abundance of insertion sequences in the genomes. In addition to full-length copies, a large number of internal deletion variants have been identified. ISSoc2 has two variants (ISSoc2∂-1 and ISSoc2∂-2) that are observed to have multiple near-exact copies. Comparison of environmental metagenomic sequences to the Synechococcus genomes reveals novel placement of copies of ISSoc2, ISSoc2∂-1, and ISSoc2∂-2. Thus, ISSoc2∂-1 and ISSoc2∂-2 appear to be active nonautonomous mobile elements derived by internal deletion from ISSoc2. Insertion sites interrupting genes that are likely critical for cell viability were detected; however, most insertions either were intergenic or were within genes of unknown function. Most novel insertions detected in the metagenome were rare, suggesting a stringent selective environment. Evidence for mobility of internal deletion variants of other insertion sequences in these isolates suggests that this is a general mechanism for the formation of miniature insertion sequences.